Inclusion Body Disease and Columbid Alphaherpesvirus 1 Infection in a Eurasian Eagle-Owl (Bubo bubo) of Central Italy - Giglia, Giuseppe; Lepri, Elvio; Orlandi, Margherita; Porcellato, Ilaria; Costantino, Isabella; Rampacci, Elisa; Passamonti, Fabrizio; Mandara, Maria Teresa; Stefanetti, Valentina (Avian Diseases, 2022)
Hepatosplenitis or inclusion body disease is a fatal disease in owls caused by Columbid alphaherpesvirus 1 (CoHV-1). A few old case reports describe it worldwide. In Italy, knowledge regarding virus circulation and disease development is lacking. Four Eurasian eagle-owls (Bubo bubo), two adults and two juveniles, were submitted for postmortem examination showing aspecific clinical signs a few hours before death. Grossly disseminated petechial hemorrhages on serosal surfaces (n = 4), hepatic and splenic necrosis (n = 3), bilateral and symmetric necrosis of pharyngeal tonsils (n = 2), and diffuse and bilateral dark-red discoloration and firmness in lungs (n = 2) were seen. Tissues were sampled for histology, bacteriology, molecular testing, and transmission electron microscopy (TEM). On histology, disseminated petechial hemorrhages (n = 4) and necrosis of liver (n = 3) and spleen (n = 3) were seen, as well as lympho-histiocytic interstitial pneumonia and meningoencephalitis (n = 2). Intranuclear inclusion bodies (INIBs) were detected in one case. A panherpesviral PCR led to positive results in one case, identified in sequencing as CoHV-1. On TEM, intranuclear and intracytoplasmic virions with herpesviral morphology were seen in the same case. For the other three birds, the lack of PCR positivity, INIBs, and TEM detection could be linked to a possible reduction of the virus to undetectable levels. Death possibly occurred secondarily to bacterial infections, supposedly established during the acute phase of CoHV-1 infection. This paper reports the presence of CoHV-1in Italy and the development of a fatal form of the disease in a Eurasian eagle-owl.